FUNGAL FLORA OF THE AIR OF BABOL CITY - S.M. Omran; M.R. Shidfar (Tehran University of Medical Sciences, 1998)
Fungal conidia and spores are among various organisms found in the air, causing different types of mycoses. In this study (from February 1994 until March 1995) fungal spores and conidia were collected by their settlement on to petri - dishes from 33 locations in Babol city during 4 seasons. Plates of sabouraud dextrose agar were laid 1.5 M. from the ground and then sent to mycology laboratory where they were incubated at room temperature. The fungi were examined by microscop and gross examination. 1520 colonies including 24 genera (Hyphomycetes 27.54% and yeast 25.46%) grew on 132 plates (11.5 colonies I plate). The most prevalent fungi isolated in this study were Cladosporiurn, yeast and Penicilliwn, Most of the colonies detected observed in summer (704 colonies), and there had been the least number of colonies isolated in winter (187 colonies).